2020
DOI: 10.22541/au.158981075.53963117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping the pressure of natural predators on pest arthropods

Abstract: Natural predators of arthropods provide an important ecosystem service by preying on crop-damaging species. However, measuring the positive impact of natural pest predators is still challenging. We present a framework to estimate the pestconsumption pressure by natural predators across space and project it onto geographical maps. We use DNA metabarcoding and species distribution modelling to integrate predator density estimations with their energetic requirements and direct pest predation, which yields a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Vegetation is indicated to be important in maintaining insect prey populations [ 15 ], while artificial lights can improve the prey capture rate of the bat species adapted to hunting in bright places [ 16 ]. Several studies have suggested the suppression of arthropods, including agricultural pests and disease vectors, by urban bats [ 17 , 18 ]. However, insectivorous species are generally poorly sampled since many studies on neotropical bats have been conducted on species more easily captured by mist nets.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation is indicated to be important in maintaining insect prey populations [ 15 ], while artificial lights can improve the prey capture rate of the bat species adapted to hunting in bright places [ 16 ]. Several studies have suggested the suppression of arthropods, including agricultural pests and disease vectors, by urban bats [ 17 , 18 ]. However, insectivorous species are generally poorly sampled since many studies on neotropical bats have been conducted on species more easily captured by mist nets.…”
Section: Introductionmentioning
confidence: 99%
“…A recent estimation suggested that a single breeding colony of 4,000–5,000 adult Miniopterus schreibersii bats preyed upon 1,610 kg of pest species over a five month period [ 17 ]. In addition, over 60 metric tons of pest arthropods were reportedly consumed daily by a subset of seven bat species across Europe [ 18 ]. Bats can thus serve both as pest controllers and ‘natural samplers’ of biodiversity, and could be used to unravel the presence and expansion of new arthropod pests.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our fourth objective was to assess ME pest species consumption, with a specific focus on taxa detrimental to forest trees and livestock. In this respect, ME provision of pest-control services remains unclear, with prior case studies drawing different conclusions [ 18 , 61 ]. However, we expected to detect stable flies ( S .…”
Section: Introductionmentioning
confidence: 99%
“…On farmland, bats consume adult insects thereby also reducing the number of laid eggs ( Boyles et al, 2013 ; Russo et al, 2018 ; Maine and Boyles, 2015 ). The first estimation of the number of insects consumed by bats in Europe was recently performed by Aizpurua and Alberdi (2020) , who calculated that six cave- and forest-dwelling species of European bats consume 63.3±13.9 metric tons of insects daily over the whole territory of Europe. However their estimations based on bat population density only for one region of Europe, and according to that the all extrapolation is far from accurate ( Aizpurua and Alberdi, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first estimation of the number of insects consumed by bats in Europe was recently performed by Aizpurua and Alberdi (2020) , who calculated that six cave- and forest-dwelling species of European bats consume 63.3±13.9 metric tons of insects daily over the whole territory of Europe. However their estimations based on bat population density only for one region of Europe, and according to that the all extrapolation is far from accurate ( Aizpurua and Alberdi, 2020 ). Birds and bats are major controllers of insect pests in fields, in tropical or neotropical forests and in agricultural landscapes ( Maas et al, 2015 ; Kimberly et al, 2008 ; Kalka et al, 2008 ; Morrison and Lindell, 2012 ).…”
Section: Introductionmentioning
confidence: 99%